2021
DOI: 10.1021/acs.orglett.1c03224
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach for 3,3-Disubstituted Oxindoles Synthesis: Aryl Iodine Catalyzed Intramolecular C–N Bond Oxidative Cross-Coupling

Abstract: Herein, we report the first intramolecular C−N bond formation of phenylpropanamide derivatives via organocatalytic oxidative reactions, affording 3,3-disubstituted oxindole derivatives with up to 99% yield. The high efficiency of this reaction is exemplified by the transition metal-free mild conditions and the ability to perform the reaction on a gram scale. Meanwhile, the DFT calculation of the catalytic oxidative transformation pathway has also been studied.O xindole scaffolds, especially 3,3-disubstituted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A tentative mechanism is proposed in Scheme 5 . The reaction commences with electrophilic activation of the C S and C O bonds by the hypervalent iodine reagent, 21 which is followed by the nucleophilic addition of amine. Subsequently, the first oxidation takes place to give thiourea 15 or urea 12.…”
Section: Resultsmentioning
confidence: 99%
“…A tentative mechanism is proposed in Scheme 5 . The reaction commences with electrophilic activation of the C S and C O bonds by the hypervalent iodine reagent, 21 which is followed by the nucleophilic addition of amine. Subsequently, the first oxidation takes place to give thiourea 15 or urea 12.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported an organocatalytic oxidative system for the intramolecular amination of C(sp 2 )–H bonds for the formation of 3,3-disubstituted oxindoles including spirocyclic derivatives. 33 Thus, an intramolecular C–N cross-coupling reaction of phenylacetamide 27 bearing cyclic alkyl substituents at the α-position afforded structurally diverse spirooxindoles 28 in 74–98% yields. The reaction employed m CPBA as the oxidant and an aryl iodide C 3 as a catalyst and was facile with N -alkoxy substituents on substrate 27 .…”
Section: Non-chiral Pathways To Spirooxindole Frameworkmentioning
confidence: 99%
“…9 Consequently, the development of efficient protocols to access these scaffolds is an active area of research in organic chemistry. The available classical synthetic routes involve: (1) C–C bond formation reactions of oxindole derived nucleophiles or electrophiles such as Michael addition between C3-substituted oxindoles and α,β-unsaturated carbonyl compounds 10 or conjugated dienes, 11 allylic substitution between C3-substituted oxindoles and allylic electrophiles, 12 Mannich reaction of isatin imines 13 and Friedel–Crafts reactions of 3-hydroxy-xyindoles with arenes; 14 (2) oxidative arylation of oxindoles; 15 (3) intramolecular annulation reaction by transition-metal-catalyzed C–H amination 16 and carbon–halogen cross-couplings of N -arylacrylamide derivatives. 17 Despite these advancements made in this research area, to exploit a new convenient process to access C3-aromatic 3,3-disubstituted oxindoles remains highly desirable and is still a challenging topic.…”
Section: Introductionmentioning
confidence: 99%